PRESERVATION OF PHYSICAL AND MENTAL HEALTH OF JUNIOR SCHOOL STUDENTS IN TIME FORMATION OF PERSISTENCE BY MEANS MOVING GAMES (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the protection o f physical and psychologic health of young pupils by means of mobile games